Feasibility of Retrohepatic Inferior Vena Cava Resection Without Reconstruction for Hepatic Alveolar Echinococcosis. Issue 3 (March 2021) - Ran, Bo; Maimaitinijiati, Yusufukadier; Yasen, Aimaiti; Jiang, Tieming; Zhang, Ruiqing; Guo, Qiang; Shao, Yingmei; Wen, Hao; Aji, Tuerganaili
This study evaluates the feasibility of retrohepatic inferior vena cava (RHIVC) resection without reconstruction in patients with end-stage hepatic alveolar echinococcosis (AE). Four hundred and fifty-seven patients diagnosed with hepatic AE and who underwent surgical resections between January 2010 and October 2018 were retrospectively analyzed. Nine patients receiving RHIVC resection without reconstruction were included in this study. Among the patients, 5 were male and 4 female. Mean follow-up time was 64.4 months (18-95). In this series, adequate collateral circulation was formed before operation in all patients, and 7 cases underwent ex vivo liver resection and autotransplantation (ELRA) and 2 cases underwent extended right hemi-hepatectomy. Average standard liver volume, graft volume, surgical time, and anhepatic phase in ELRA group patients was 1144 ± 127 cm 3, 740 ± 235 cm 3, 16.8 ± 4.1 hours, and 337.4 ± 108.65 minutes respectively. Average hospital stay time for all patients was 45 ± 36.4 days. There were no intraoperative deaths. The 30-day mortality rate was 11.1%, and total mortality rate was 22.2%. Postoperative complications occurred in 4 patients. During follow-up, no relapsed AE lesions were found. RHIVC resection without reconstruction is a feasible way for hepatic AE patients with adequate collateral circulation. Careful protection of collateral venous is the key factor for successful operation.